Clinical risk factors associated with multidrug-resistant tuberculosis (MDR-TB) in Mali. (April 2019) - Baya, Bocar; Achenbach, Chad J.; Kone, Bourahima; Toloba, Yacouba; Dabitao, Djeneba K.; Diarra, Bassirou; Goita, Drissa; Diabaté, Seydou; Maiga, Mamoudou; Soumare, Dianguina; Ouattara, Khadidia; Kanoute, Tenin; et al.
Highlights: MDR-TB was associated with younger age in Mali. HIV was not a risk factor for MDR-TB. MDR-TB did alter the patient's physical condition compared to susceptible TB. Tobacco consumption did not increase the risk of developing MDR-TB. Abstract: Background: MDR-TB is a major threat to global TB control. In 2015, 580, 000 were treated for MDR-TB worldwide. The worldwide roll-out of GeneXpert MTB/RIF ® has improved diagnosis of MDR-TB; however, in many countries laboratories are unable to assess drug resistance and clinical predictors of MDR-TB could help target suspected patients. In this study, we aimed to determine the clinical factors associated with MDR-TB in Bamako, Mali. Methods: We performed a cross-sectional study of 214 patients with presumed MDR-TB admitted to University of Bamako Teaching Hospital, Point-G between 2007 and 2016. We calculated crude and adjusted odds ratios for MDR-TB disease diagnosis using SPSS. Results: We found that age ≤40 years (OR = 2.56. 95% CI: 1.44–4.55), two courses of prior TB treatment (OR = 3.25, 95% CI: 1.44–7.30), TB treatment failure (OR = 3.82, 95% CI 1.82–7.79), sputum microscopy with 3+ bacilli load (OR = 1.98, 95% CI: 1.13–3.48) and a history of contact with a TB patient (OR = 2.48, 95% CI: 1.11–5.50) were significantly associated with confirmation of MDR-TB disease. HIV was not a risk factor for MDR-TB (aOR = 0.88, 95% CI: 0.34–1.94). Conclusion: We identified several risk factors that could be used to identify MDR-TB suspects and prioritize them for laboratory confirmation. Prospective studies are needed to understand factors associated with TB incidence and clinical outcomes of TB treatment and disease.